Ofo Anam regards sur une statuaire igbo - Espenel, Alexandre (Galerie l'Accrosonge, 2001)
Forty Igbo sculptures exhibited at the Accrosonge Gallery
Keywords: Sculpture, African / Nigeria; Wood sculpture, Igbo / Nigeria